ENERGY NOT SOLD (ENS) PADA IMPLEMENTASI FAULT DETECTION INSULATION AND RESTORATION (FDIR) PT. PLN DI PENYULANG OGAN GARDU INDUK SEI JUARO - Fithri, Normaliaty; Fitriani, Endah (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2020)
As an effort to carry out sustainability services with efficient distribution of electricity quality, a system that can provide a form of service with reliable distribution system is implemented that can provide an overview of the narrowing of the territory of the extent of the disturbance that is happening. With the application of the Fault Detection Insulation and Restoration (FDIR) system in the feeder with a relatively fast and automatic maneuver process, it can reduce the duration of the outage which can also directly determine the point of disturbance when a disturbance occurs in real time. If there is a disturbance in the Ogan feeder, the FDIR automation system will immediately isolate the network by maneuvering the Kedondong feeder in less than one minute, so that by calculating ENS you can get the benefit of reducing the Energy not sold (ENS) value.